Innovation in the Development of the Toddler Family Development Program in Air Raya, Bandarsyah Village, East Bunguran District, Natuna Regency, Riau Islands - Evline, Evline; Muchlis, Maulana; Daulay, Pardamean (Jurnal Ilmu Kesehatan, 2024)
This research aims to develop innovation in the Toddler Family Development Program (BKB) in Air Raya, Bandarsyah Village, East Bunguran District, Natuna Regency, Riau Islands. The BKB program is a government initiative which aims to improve the welfare and development of toddlers through education and guidance to parents regarding good parenting patterns, health and child nutrition. This research uses a qualitative approach with data collection techniques through in-depth interviews, observation and documentation. Research respondents included BKB program implementers, parents who participated in the program, and related health workers. Data analysis was carried out thematically to identify needs and potential for innovation in implementing the BKB program. The research results show that innovation in the BKB program at Air Raya can increase family participation and the quality of interaction between parents and toddlers. Some of the proposed innovations include: the use of information technology such as mobile applications to provide information on the health and development of toddlers and as a means of communication between parents and BKB officers; holding regular training and workshops for parents on parenting, nutrition and children's health; increasing collaboration with community health centers, posyandu, and educational institutions to provide more comprehensive services; and implementing mobile education programs that can reach families living in remote areas.